A Pre Experimental Study: The Effect of Blanket Warmers on Increasing Temperature in Post Caesarean Section Hypothermia Patients - Astrida Budiarti; Miftaqul Jannah; Puji Hastuti (Universitas STRADA Indonesia, 2026)
Background: Caesarean section is one of the most frequently performed surgical procedures, commonly using spinal block anesthesia. One of the common side effects of spinal anesthesia is hypothermia. Purpose: The aim of this study was to analyze the effect of using a blanket warmer on increasing body temperature in post caesarean section patients experiencing hypothermia following spinal anesthesia. Methods: This study employed a pre-experimental design with a pre-posttest approach. The population consisted of all caesarean section patients undergoing spinal anesthesia, totaling 23 individuals. The sampling technique used was non-probability purposive sampling, with a final sample size of 23 patients. Data collection was carried out using observation sheets. Statistical analysis was performed using the paired sample t-test. Results: The findings showed that the mean body temperature before intervention of the blanket warmer was 36.10 °C, and after the intervention, the mean temperature increased to 36.67°C. The paired sample t-test revealed a statistically significant difference with a p-value of 0.000, which is lower than the significance level of α = 0.05. Conclusion: Blanket warmer significantly increases body temperature in post caesarean section patients receiving spinal block anesthesia. Blanket warmers are effective in addressing hypothermia as they provide controlled heat transfer, allowing patients with hypothermia to absorb heat from the device.